2012
DOI: 10.1007/s10048-012-0320-2
|View full text |Cite
|
Sign up to set email alerts
|

Forkhead family transcription factor FoxO and neural differentiation

Abstract: The Forkhead Box subgroup O (FoxO) transcription factor family is one of the most important downstream targets of the phosphatidylinositol 3-kinase/protein kinase B signaling pathway playing an important role in many biological functions including transcriptional regulation of cellular differentiation. Neuronal differentiation is a complex process which involves many signaling pathways and molecular mechanisms. Interestingly, recent studies indicate that the FoxO family is involved in a number of signaling pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 95 publications
(64 reference statements)
1
17
0
Order By: Relevance
“…As a transcription factor, forkhead family protein plays important roles in cell cycle regulation, embryonic development, lipid and carbohydrate metabolism, aging, immune regulation, and other biological processes 4,23,24. As a member of forkhead family protein, in mammals, FOXQ1 was initially found to take part in hair follicle development 8.…”
Section: Discussionmentioning
confidence: 99%
“…As a transcription factor, forkhead family protein plays important roles in cell cycle regulation, embryonic development, lipid and carbohydrate metabolism, aging, immune regulation, and other biological processes 4,23,24. As a member of forkhead family protein, in mammals, FOXQ1 was initially found to take part in hair follicle development 8.…”
Section: Discussionmentioning
confidence: 99%
“…Through regulation via the PI3K/Akt pathway, many of downstream target genes of FasL,MnSOD,p27,PEPCK) are regulated and these gene products play roles in cell proliferation (p27), differentiation (Btg-1), metabolism (PEPCK) , apoptosis (Bim-1, FasL) and drug resistance (Wen et al, 2012;van der Vos and Coffer, 2011;Hui et al, 2008). For example, sustained FoxO3a activation promotes drug resistance by activating and promoting the expression of ATP-binding cassette sub-family B member 1, which is a plasma membrane P-glycoprotein that functions as an efflux pump for various anticancer agents, including doxorubicin (Hui et al, 2008).…”
Section: Overview Of Foxo Signaling Pathwaymentioning
confidence: 99%
“…The PI3K/Akt signal pathway plays a critical role in mediating neuronal survival. FoxO regulates the expression of genes involved in neuronal cell apoptosis and oxidative stress, such as Bim-1, FasL, Catalase and MnSOD (Brunet et al, 2001a, Wen et al, 2012. The pattern of protein distribution related to FoxO functions points to the associated biological functions.…”
Section: Foxo Expression Patterns In the Brainmentioning
confidence: 99%
See 1 more Smart Citation
“…metabolism, cell cycle regulation, aging, immune regulation and other biological processes [15][16][17]. Initial studies indicated that FOXQ1 took part in hair follicle development in mammals [18], hereafter FOXQ1 overexpression was found in colorectal cancer, gastric cancer, bladder cancer, liver cancer, breast cancer, nonsmall cell lung cancer, and ovarian cancer [19][20][21].…”
Section: Introductionmentioning
confidence: 98%